Relationship between Adherence to Therapeutic Regimen and Health Related Quality of Life in Hypertensive Patients - DD Masror Roudsari; M Dabiri Golchin; Z Parsa yekta; H Haghani (Iran University of Medical Sciences, 2013)
Abstract   Background & Aims: patient compliance with therapeutic regimen predicts successful treatment and reduces the severity of negative complications. The aim of this study was determination of relationship between adherence to therapeutic regimen and health related quality of life in hypertensive patients in 2012.   Material & Methods: It was a descriptive- correlational study. The hypertensive patients (n=264) were recruited by convenience sampling. Data was collected by demographic sheet, and Adherence to Treatment tool and health-related quality of life questionnaire (SF-36). The setting was selected hospitals affiliated to Tehran and Iran University of Medical Sciences including Imam Khomeini Hospital, Hazrat Rasoul Akram Hospital and Shahid Rajai hospital. Data was analyzed by T-Test and ANOVA and Linear Regression using SPSS-PC (v.16).   Results: Most of Participants were 40-60 year old males. In most of patients adherence to diet was relatively good (79.5%), compliance with drug regimen was good (48%) and activity was poor (71%) and adherence to therapeutic regimen was relatively good (82%). Mean score of quality of life among hypertensive patients was 55.33. There was a significant relationship between quality of life and adherence to treatment using Pearson correlation test (p=0.001, r=0.671).   Conclusion: Regarding the relationship between adherence to therapeutic regimen and health- related quality of life in this sample, teaching hypertensive people to increase their adherence and their quality of life is suggested.   Reveived: 6 Oct 2013   Accepted: 24 Dec 2013